Mitral Plasticity: The Way to Prevent the Burden of Ischemic Mitral Regurgitation? - Vinciguerra, Mattia; Romiti, Silvia; Wretschko, Eleonora; D'Abramo, Mizar; Rose, David; Miraldi, Fabio; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2022)
The ischemic impairment of the left ventricular contractility, followed by an adverse remodeling leading to the displacement of the papillary muscles (PMs), increased tethering forces and loss of valve competence has been the long-term accepted definition of ischemic mitral regurgitation (IMR). Over the years, different approaches of management have attempted to address valve regurgitation, nevertheless failing to achieve satisfactory outcomes. Recent studies have observed some structural and molecular changes of the mitral valve (MV), challenging the concept of a bystander passive to the subvalvular involvement. Indeed, the solely mechanical stretch of the PMs, as in the dilated left ventricle because of the aortic valve regurgitation, is not enough in causing relevant MV regurgitation. This setting triggers a series of structural changes called “mitral plasticity,” leaflets increase in their size among others, ensuring an adequate systolic area closure. In contrast, the ischemic injury not only triggers the mechanical stretch on the subvalvular apparatus but is also a powerful promotor of profibrotic processes, with an upregulation of the transforming growth factor (TGF)-β signaling pathway, leading to a MV with exuberant leaflet thickness and impaired mobility. In this article, we revise the concept of IMR, particularly focusing on the new evidence that supports dynamic changes in the MV apparatus, discussing the consequent clinical insights of “mitral plasticity” and the potential therapeutic implications.